Considering Work Arrangement as an “Exposure” in Occupational Health Research and Practice - O'Connor, Allyson; Peckham, Trevor; Seixas, Noah (Frontiers in Public Health, 2020)
Most occupational health research is conducted with the so-called “standard employment relationship” in mind, which entails ongoing, full-time employment for a single employer. Yet mounting evidence suggests the way work is organized is increasingly deviating from this standard model, and that work arrangements themselves—the terms and conditions of employment such as contract type and the extent of directive control over tasks—are important determinants of worker health and safety. However, a lack of clear conceptual definitions or taxonomic system defining the wide variety of economic work arrangements in the contemporary workplace hampers rigorous investigation of their relationship to health. The various forms of “non-standard” employment arrangements—also called non-traditional, alternative, flexible, fissured, precarious, contingent, temporary, atypical, or gig work—may have overlapping attributes, yet ambiguity regarding the character of these arrangements obscures mechanisms that lead to increased health and safety risks. Here, we attempt to clarify work arrangements as a workplace exposure, deserving of specific attention within occupational health and safety research, practice, and policy. We argue that, at minimum, three key features of work arrangements need to be considered: (1) whether an arrangement is permanent or temporary; (2) whether a worker is a contractor or an employee; and (3) whether an arrangement involves more than one firm. We further propose mechanisms linking work arrangements to increased work-related health risks to better inform strategies aimed at protecting the growing non-standard workforce.